1997
DOI: 10.1006/viro.1997.8580
|View full text |Cite
|
Sign up to set email alerts
|

Avian Influenza A Viruses Differ from Human Viruses by Recognition of Sialyloligosaccharides and Gangliosides and by a Higher Conservation of the HA Receptor-Binding Site

Abstract: Avian influenza virus strains representing most hemagglutinin (HA) subtypes were compared with human influenza A (H1N1,H3N2) and B virus isolates, including those with no history of passaging in embryonated hen's eggs, for their ability to bind free N-acetylneuraminic acid (Neu5Ac) and sialylollgosaccharides in a competitive binding assay and to attach to gangliosides in a solid-phase adsorption assay. The avian viruses, irrespective of their HA subtype, showed a higher affinity for sialyl-3-lactose and the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
293
2
5

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 371 publications
(307 citation statements)
references
References 30 publications
7
293
2
5
Order By: Relevance
“…(1999) galactose by the ␣2,3 linkage (SA␣2,3Gal), whereas humanadapted HAs prefer the ␣2,6 linkage (SA␣2,6Gal). A shift from SA␣2,3Gal to SA␣2,6Gal binding seems to be a critical step in the adaptation of an avian HA to the human host (20,22,23). Determining the minimal changes allowing avian H1s to function in humans is complicated by the fact that the earliest H1 strains have been maintained in different laboratory host cells, a practice that selects for mutations in the receptor-binding sites (20).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1999) galactose by the ␣2,3 linkage (SA␣2,3Gal), whereas humanadapted HAs prefer the ␣2,6 linkage (SA␣2,6Gal). A shift from SA␣2,3Gal to SA␣2,6Gal binding seems to be a critical step in the adaptation of an avian HA to the human host (20,22,23). Determining the minimal changes allowing avian H1s to function in humans is complicated by the fact that the earliest H1 strains have been maintained in different laboratory host cells, a practice that selects for mutations in the receptor-binding sites (20).…”
Section: Resultsmentioning
confidence: 99%
“…The 1918 sequence, having been derived directly from viral RNA, is free of any possible artifacts of laboratory adaptation. A subset of amino acids that are unvaried in all avian HAs but vary in mammalian-adapted HAs has been identified (23) and constitutes the minimum receptor-binding site. Changes in these amino acids have been shown to affect receptor-binding specificity (24) and antigenicity (25).…”
Section: Resultsmentioning
confidence: 99%
“…Korean field isolates are less productive in ECE, and their productivities should be improved prior to use in vaccine development [9,16,17]. The efficiency of influenza virus replication in ECE can be affected by the receptor affinity of HA, the balance of HA and NA activities, and internal genes [13,[18][19][20][21][22][23]. A good vaccine candidate should be cost-effective in production, antigenically representative of contemporary field strains, and safe for chickens and mammals.…”
Section: Introductionmentioning
confidence: 99%
“…S2 Fig. S1 available in JGV Online) (Matrosovich et al, 1997(Matrosovich et al, , 2000. Interestingly, Kaverin et al.…”
mentioning
confidence: 99%
“…Additional amino acid differences in the receptor-binding pocket of A/ Hebei/52/94 and A/Beijing/262/95 HAs, including residues 190, 225 and 226 (H3 numbering) known to impact receptor specificity, may play a role in magnifying the effect of deleting residue 134 in A/Hebei/52/94 HA ( Supplementary Fig. S1 available in JGV Online) (Matrosovich et al, 1997(Matrosovich et al, , 2000. Interestingly, Kaverin et al (2000) reported that virus aggregation, resulting from incompatibilities between the HA and NA glycoprotein activities, could be overcome by mutation in the vicinity of the receptor pocket of HA by increasing the local negative charge.…”
mentioning
confidence: 99%